Northwest Native Plants: A Digital Space for Paleoethnobotanical Knowledges and Biocultural Heritage - Molly Carney; Melanie Diedrich; John C. Blong; Jade d’Alpoim Guedes; Tiffany J. Fulkerson; Tiffany Kite; Katy Leonard-Doll; Joyce LeCompte-Mastenbrook; Mario Zimmermann; Shannon Tushingham (Heritage, 2022)
Biocultural heritage preservation relies on ethnobotanical knowledge and the paleoethnobotanical data used in (re)constructing histories of human–biota interactions. Biocultural heritage, defined as the knowledge and practices of Indigenous and local peoples and their biological relatives, is often guarded information, meant for specific audiences and withheld from other social circles. As such, these forms of heritage and knowledge must also be included in the ongoing data sovereignty discussions and movement. In this paper we share the process and design decisions behind creating an online database for ethnobotanical knowledge and associated paleoethnobotanical data, using a content management system designed to foreground Indigenous and local perspectives. Our main purpose is to suggest that the Mukurtu content management system, originally designed for physical items of cultural importance, be considered as a potential tool for digitizing and ethically circulating biocultural heritage, including paleoethnobotanical resources. With this database, we aim to create access to biocultural heritage and paleoethnobotanical considerations for a variety of audiences while also respecting the protected and sensitive natures of Indigenous and local knowledges.